Properties and anisotropy behaviour of a nickel base alloy material produced by robot-based wire and arc additive manufacturing - Hassel, Thomas; Carstensen, Torben (Welding in the world, 2020)
In order to produce three-dimensional components from metals, a wide variety of processes exist. Laser processes combined with metal powders are frequently used and developed. Restrictive factors are the machine-related small workspace, the machinery costs and the material portfolio, which place the technology in the area of high-performance components. Wire and arc additive manufacturing (WAAM), as a robust and economical welding process technology in combination with robot applications, represents an option to become more size-independent and provides variability in the range of materials. This work shows results for the robot-based WAAM of structures made from nickel alloy 617. The main focus of the investigation was the determination of the mechanical properties in the as-welded state for which static strength tests, microhardness and metallographic studies were carried out. The anisotropic material behaviour in relation to the build direction (BD) was tested. The direction-dependent strength properties of single-track welded structures are presented with samples taken and tested at 0°, 45° and 90° to the BD. The deformation behaviour was investigated by micro-tensile tests in a scanning electron microscope, whereby the formation of sliding steps on the polished surface under tensile stress was studied. The anisotropic behaviour of the WAAM structures is discussed under consideration of the microstructure and with regard to the grain size development and phase formation. The results indicate an anisotropic material behaviour in the as-welded state based of the crystallographic orientation of the material.